Pengaruh Pelaksanaan Sistem Pengendalian Internal, Kompleksitas Operasional Perusahaan, dan Kompetensi Auditor Internal terhadap Audit Delay: Studi Empiris pada Perusahaan Barang Konsumsi Non-Primer yang Tercatat di BEI Tahun 2019-2022 - Lukman, Finda; Syofyan, Efrizal (Jurnal Eksplorasi Akuntansi, 2024)
The objective of this study is to examine the effect of implementing an internal control system, operational complexity of the company, and competence of internal auditors on audit delay. The study utilizes annual reports from consumer cyclicals sector companies listed on the Indonesia Stock Exchange (IDX) that were delayed in 2019-2022. Purposive sampling was used to collect data, with a total sample of 170 comapnies. Multiple linear regression analysis was employed to test the hypothesis. The study found that the implementation of the internal control system had a negative and significant effect on audit delay, complexity of the company’s operations had a positive but not significant on audit delay, and the competence of the internal auditors had no effect on audit delay.